Effect of Deformation of Ti-3Al-8V-6Cr-4Zr-4Mo Alloy under Varying Thermo-Mechanical Conditions on its Microstructure and Deformation Behavior - S. Tomasik; A. Łukaszek-Sołek; T. Śleboda; Ł. Lisiecki (Archives of Metallurgy and Materials)
This paper analyses the impact of thermomechanical processing history on the microstructure and thermomechanical behavior of Ti-3Al-8V-6Cr-4Zr-4Mo titanium alloy. The alloy was deformed in compression at various temperatures and strain rates, and the flow stress curves were elaborated basing on the testing data. The analysis of the material behavior at different temperature and strain rate ranges was performed taking into account various criteria of stability and instability of the material flow (Semiatin-Lahoti criterion and Murty’s criterion) under various thermomechanical conditions. It was shown, that the inhomogeneity of the alloy’s microstructure in the initial state, mainly due to its crystallization conditions, is also a significant factor that affects the inhomogeneity of deformation. The study indicates that the analyzed alloy needs to undergo heat treatment to homogenize its structure before it can be subjected to processing. The processing maps developed using both the Semiatin-Lahoti and Murty criteria were found to be effective in predicting flow instability and optimising hot forming parameters. The maps highlighted regions susceptible to adiabatic shear bands and strain localisation, while also identifying optimal conditions for dynamic recrystallisation and material softening. The results of this study may have direct applications in the design of thermomechanical processing of the studied titanium alloy under industrial conditions.